BEAUTY(NESS) AND SUBLIME(ITY) IN BIR KADIN DUSMANI (A MISOGYNIST) - Yasemin ALPER (Fırat University, 2019)
Aesthetic, whose foundations were laid in mid- 18’s by A. G. Baumgarten, is a discipline founded upon studying beauty (ness) concept. While aesthetic covers fields of intuition, enthusiasm, and feeling, it is also regarded as a philosophy branch which details the descriptive story of things and existence. In the early periods, aesthetic was interested in the beauty and something beautiful in a sensual context. However in the following periods, something sublime, naive, ugly, terrifying, and scary was studied in the aesthetic category as well. Also, Kant studied aesthetics to find out what elements caused in a person to feel beauty in it and tried to examine the sublime too in an effort to involve both of them as aesthetic elements. In Resat Nuri Guntekin’s Bir Kadın Dusmanı novel, one of the authors who wrote many pieces in Turkish literature, efforts to put aesthetic elements forward were perceived. The degree to which the depictions of nature and people in this novel were in line with Kant’s concepts of the “beauty” and “sublime” which are revealing the aesthetic was researched. In this context, even though the beauty of Sâra, who is one of the heroes in novel, is in such a perfection that people in real life can take pleasure, the author faced his readers with the questions of “Is Sâra beautiful in reality?” and he questioned another hero’s, Homongolos, ugliness of appearance with the question of “Is it an obstacle for Homongolos to be sublime?”. The author does not directly ask these questions, and lead the readers to react and give answers to these questions on their own. Studying the novel by the concepts of “beauty” and “sublime”, which are mentioned in Kant’s “Observations on the Feeling of the Beautiful and Sublime”, the answers to whether Sâra is “beautiful” or Homongolos is “ugly” or “sublime” are analyzed.